Das Cogito als Fundament des Wissens - Dierig, Simon (History of philosophy & logical analysis, 2022)
Abstract In this essay, I discuss three readings of Descartes’ Meditations. According to the first reading, “I exist” is for Descartes the foundation of our knowledge. This reading is dismissed on the grounds that, in his view, as long as God’s existence is not proven there is a good reason to doubt this proposition. Proponents of the second reading claim that there are two kinds of Cartesian knowledge: perfect and imperfect knowledge. The meditator has imperfect knowledge of “I exist” before God’s existence is proven. Subsequently, she acquires perfect knowledge of various metaphysical theorems. This reading is repudiated, too. I argue for a third reading, according to which “I think” - and not “I exist” - is the foundation of our knowledge.